Quelle sorte de majorit\IeC é, ou comment d\IeC éterminer les laur\IeC éats d\IeC {’ }un concours? - Laurencelle, Louis (Tutorials in Quantitative Methods for Psychology, 2018)
Determining the final ranking of a set of candidates individually classified by two or more judges is carried out using different proposed rules, each rule giving a somewhat original and sometimes paradoxical result. The known calculation rules are defined, exemplified and analyzed, as well as some new ones. Finally, pragmatic suggestions to help obtain a satisfying outcome are given.